Trapezio-metacarpal arthritis: functional and radiographic results at an average 5-year follow-up using trapeziectomy associated to a modified Ceruso’s suspensionplasty. - Concina, Chiara; Crucil, Marina; Saggin, Giorgio; Gherlinzoni, Franco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Trapezial-metacarpal arthritis (TMA) is a common and highly disabling pathology. Trapeziectomy and Ceruso’s suspensionplasty is described for moderate-severe stages. The aim of the present study was to assess functional and radiographic results at an average 5-year follow-up using a modified Ceruso’s technique where the Abductor Pollicis Longus (APL) is passed twice around the Flexor Carpi Radialis (FCR) and a suture mini-anchor in the base of the first metacarpal is used to further stabilize the thumb. Methods: 85 consecutive modified Ceruso’s suspensionplasty were performed from 2012 and 2018. All the patients were evaluated at an average 5.1-year follow-up (21-96 months). Subjective patient satisfaction rate, NRS, DASH score, abduction angle, Kapandji score and pinch strength using functional tests were assessed. The scapho-metacarpal distance was measured at follow-up radiographs. Results: 90.6% of the patients were satisfied by the treatment. The NRS and the DASH score improved (from 8.5 pre-operatively to 1.53 and from 87.5 to 24.6 respectively-p<0.001). The Kapandji test was rated from 7 to 10 in 65.9% of the patients. The pinch strength was good in 75.3% of the patients at follow-up. The abduction angle of the thumb was 38.2° (20°-55°). The mean scapho-trapezial distance decreased of 2.45 mm (from 9.87 mm to 7.42 mm - p<0.05). 8 patients had persistent pain and thumb disfunction, 1 patient had De Quervain’s tenosynovitis. Conclusions: Suspensionplasty according to Ceruso’s is a relatively simple and reproducible technique for moderate-severe TMA. It improves pain and thumb function, giving good stability without significant shortening.